Work Posture Analysis Using Rula Method To Minimize Musculoskeletal Disorders Complaints Among Doctors At Pt Rusunda Medika Abadi - Illahi, Rizki Nur; Winarno, Winarno (Institut Teknologi Nasional, Bandung, 2025)
In the current industrial era, Indonesia is experiencing significant developments in the competition of goods and services. Business actors compete with each other to dominate market share, which drives them to develop innovations and improve productivity. The human factor is a key element in enhancing company performance, where effective management can improve efficiency and productivity. This research focuses on PT Rusunda Medika Abadi, a healthcare company specializing in male circumcision. The company faces challenges related to poor posture among doctors during procedures, caused by the use of manual techniques, which can lead to fatigue and musculoskeletal issues, ultimately affecting performance and workplace safety. This activity poses a risk of causing musculoskeletal disorders complaints among the workforce. Therefore, a posture analysis of the doctor was conducted to identify those risks and provide improvement suggestions. The Rapid Upper Limb Assessment (RULA). methods is used to assess the workers' posture during activities. The research results are expected to provide improvement recommendations in accordance with ergonomic and biomechanical principles, thereby enhancing worker performance and health as well as reducing the risk of injury.